Research on online teachers’ training based on the gamification design: A survey analysis of primary and secondary school teachers - Tiezhu Liu; Mohamed Oubibi; Yueliang Zhou; Antony Fute (Heliyon, 2023)
The current form of teacher education and training has gradually shifted to distance training, but the most prominent performance of the participants in network training is the lack of motivation and enthusiasm for participation, and the participants participate in the training with the mentality of coping with the assessment, and the training effect is naturally not very good. At this point, the concept of gamification learning has become popular. Gamification applies game thinking and mechanics to non-game areas to guide user interaction and use. Based on Professor Kevin Werbach's gamification design framework, this study developed a case study of gamification for online teacher training, implemented in a professional development program for primary and secondary school teachers in Zhejiang Province, China. A self-administered questionnaire was then surveyed in three teaching classes, and the results found that: Firstly The participants' satisfaction in response to the gamification case was at a moderate to high level (M > 4.0, Tot = 5.0); Secondly, demographic factors did not significantly influence this (p > 0.05); Thirdly, among the gamification design influencing factors, presentation and feedback were the most influential (b = 0.536,p = 0.000), goals and rules (b = 0.167, p = 0.012), communication and interaction (b = 0.155, p = 0.029), and personalization (b = 0.154, p = 0.020) in decreasing order; Fourthly, The effect of case implementation significantly impacted participants' intention to sustain participation (b = 0.874, p = 0.000). Finally, we distilled the study's shortcomings and the prospects for future research.